Konsep Diri, Stres, dan Prokrastinasi Akademik pada Mahasiswa - Indah Handayani, Sri Wiworo Retno (Persona:Jurnal Psikologi Indonesia, 2012)
Abstract. The present research aims to find the correlation between self concept and stress with academic procrastination.  The research sbjects were 337 students of faculty of psychology,Wisnuwardhana University. Data for this research were obtained by self concept scale, stress scale and academic procrastination scale. The data then were analyzed  using SPSS for Windows 17, with regression analysis technique and then partial correlation.  The results of regression analysis showed the significant correlation between self concept, stress and academic procrastination. The results of partial correlation analysis  showed the negative correlation between self concept and procrastination, and other while, no correlation  between stress and procrastination.Keywords : self concept, stress, procrastination